The feasibility of a clinical audit tool to investigate stillbirth in Australia – a single centre experience. (23rd March 2018) - Lehner, Christoph; Harry, Amanda; Pelecanos, Anita; Wilson, Lauren; Pink, Kate; Sekar, Renuka
Abstract : Background: The stillbirth rate in Australia is 7 per 1000 births (Australia's Mothers and Babies 2014—in brief. Perinatal Statistics Series no. 32. Cat no. PER 87, Canberra, AIHW, 2016). The Perinatal Society of Australia and New Zealand (PSANZ) developed guidelines to standardise the investigations into stillbirth. Aims: To identify causes of stillbirths and stillbirth care using the National Perinatal Death Clinical Audit Tool (National Perinatal Death Clinical Audit Tool, Australian and New Zealand Stillbirth Alliance [ANZSA]/Perinatal Society of Australia and New Zealand [PSANZ]) and compare it to the PSANZ recommendations. Documentation of examination findings and follow‐up after stillbirth were also reviewed. Materials and Methods: From the total of 515 registered stillbirths at a Queensland hospital, 170 stillbirths were considered unexplained after chart review between July 2004 and September 2014. The National Perinatal Death Clinical Audit Tool was applied and resulting underlying causes of stillbirths were classified using the PSANZ perinatal mortality classification system. Results: The stillbirth rate for this centre was 11.2 per 1000 births. A cause of fetal death was established in 55.4% (93/168) and 75 cases (44.6%) remained unexplained corresponding to 14.6% of all registered stillbirths (75/515). Over half of the women (52.7%) were nulliparous. High rates of autopsy (47.3%), bereavement support (99.4%) and placental histopathology (98.8%) were noted. The general practitioner was notified in 98.7% of cases at the time of stillbirth; 34.1% of babies were small for gestational age at birth, 18.9% were growth‐restricted at birth and 21.4% of women were current smokers. Conclusion: The National Perinatal Death Clinical Audit Tool facilitates and streamlines stillbirth investigations and thus helps to identify underlying causes of stillbirth.